Milestones of the discipline of public administration (Note) - Sharma, Rajesh (1996)
The author briefly discusses the progress of the discipline of modern Public Administration through traversing different approaches, and elaborates on New Public Administration's two phases-Phase I and Phase II-in a bid to cover the latest developments. - Reproduced
Keywords: Note; Public administration